Are sTWEAK and IL-17A Levels in Inflammatory Bowel Disease Associated with Disease Activity and Etiopathogenesis?. Issue 3 (March 2016) - Kaplan, Mustafa; Yuksel, Mahmut; Ates, Ihsan; Yalın Kilic, Zeki Mesut; Kilic, Hasan; Ates, Hale; Kayacetin, Ertugrul
Abstract : Background: We aimed to identify the levels of soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and interleukin 17A (IL-17A) in inflammatory bowel disease (IBD) and to examine their relationship with disease activity. Methods: A total of 92 patients with IBD, in which 54 patients were diagnosed with ulcerative colitis and 38 patients with Crohn's disease (CD), and 104 healthy controls were included in the study. The Rachmilewitz endoscopic activity index was calculated in ulcerative colitis, and the CD activity index was calculated in CD. Results: sTWEAK ( P < 0.001) and IL-17A ( P = 0.006) levels were higher in the IBD group than in the control group. Both in the IBD group and ulcerative colitis and CD subgroups, in active patients, sTWEAK and IL-17A levels were found to be higher than in inactive and control groups. In the IBD group, a positive correlation was determined between sTWEAK and IL-17A, and C-reactive protein, endoscopic activity index, and CD activity index. In multivariable regression analysis, C-reactive protein and sTWEAK levels were determined to be an independent risk factor for both endoscopic activity index and CD activity index. In receiver operating curve analysis, the sTWEAK level was determined to predict IBD with high sensitivity and specificity with a value of >588.34 pg/mL and activity with a value of >669.28 pg/mL. Conclusion: Based on these results, we ascertain that sTWEAK has a role in etiopathogenesis of IBD. In addition, we believe that sTWEAK could be used as a marker for both disease activity criteria and treatment monitoring. Abstract : Article first published online 9 December 2015.